Corporate Governance and its Impact in Company’s Stock Price: Case Study - PRABOWO, BAHTIAR; ROCHMATULAILI, ENY; RUSDIYANTO, RUSDIYANTO; SULISTYOWATI, ENY (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This study aims to evaluate the application of good corporate governance to the stock prices of Indonesian manufacturing companies. It is used a descriptive method with a quantitative approach. The population in this study is the manufacturing companies in Indonesia from 2016 to 2018. The research data uses secondary information, and financial statements of the companies. The results of the study indicate that the Independent Commissioner and Managerial Ownership have an impact on stock prices, while the Institutional Ownership does not have an impact. RESUMEN Este estudio tiene como objetivo evaluar la aplicación de la buena gobernabilidad corporativa a los precios de las acciones de las empresas manufactureras indonesias. Se utiliza un método descriptivo con un enfoque cuantitativo. La población en este estudio está compuesta por las empresas manufactureras indonesas de 2016 a 2018. Los datos de la investigación utilizan información secundaria, tales como los estados financieros de dichas empresas. Los resultados del estudio indican que el Comisionado Independiente y la Propiedad Administrativa tienen un impacto en los precios de las acciones, mientras que la Propiedad Institucional no tiene impacto.